2018
DOI: 10.1093/workar/way004
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Workplace Accommodation Needs, Use and Unmet Needs Among Older Workers With Arthritis, Diabetes and No Chronic Conditions? Examining the Role of Health and Work Context

Abstract: The aging of workforces combined with the prevalence of age-related chronic diseases has generated interest in whether large numbers of older workers will need workplace accommodations. This research applied work functioning theory to examine accommodation availability, need and use in workers with arthritis, diabetes, or no chronic disabling diseases; factors associated with accommodation needs; and the relationship of accommodation needs met, unmet or exceeded to job outcomes. Participants were aged 50–67 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Participants were asked about their need for six benefits or accommodations to help manage disability at work. 22 They were prescription drug coverage; extended health benefits; flexible work schedules; modified job duties; work from home arrangements; and an accessible workplace, workstation adaptations, and/or assistive devices or technology. A score from 0 to 6 was created by summing the number of accommodations respondents reported needing but that were not available.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked about their need for six benefits or accommodations to help manage disability at work. 22 They were prescription drug coverage; extended health benefits; flexible work schedules; modified job duties; work from home arrangements; and an accessible workplace, workstation adaptations, and/or assistive devices or technology. A score from 0 to 6 was created by summing the number of accommodations respondents reported needing but that were not available.…”
Section: Covariatesmentioning
confidence: 99%
“…Workers living with a disability will report significantly different work context and job conditions than workers with no disability. 21 , 22 , 23 This includes less income, less job control, being less willing to share work-related support needs, and greater job stress and perceived job lock.…”
Section: Introductionmentioning
confidence: 99%
“…A study on organizations in that province found that workers suffering from chronic illness whose accommodation needs were exceeded by existing workplace accommodation practices reported better job outcomes than those whose accommodation needs had been unmet or merely met without being exceeded. The authors conclude that work context rather than health conditions was the source of unmet accommodation needs and that better accommodation policies and practices were key to maintaining older workers and those with chronic conditions in the workforce (Gignac et al 2018).…”
Section: Rules Governing Human Rights and Protections Against Discrimmentioning
confidence: 99%
“…This research suggests that the provision of supports within the workplace has the potential to ameliorate the impact of rheumatic disease in ways that strengthen person-job fit and minimize productivity loss. The workplace supports that are in the highest demand as reported by people with rheumatic disease include scheduling accommodations, extended medical/drug benefits, adaptations to the physical work environment, modified job duties, and workplace social support (8,10,11,27,28).…”
Section: Introductionmentioning
confidence: 99%